Intimate partner violence during pregnancy against 601,534 women aged 15 to 49 years in 57 LMICs: prevalence, disparities, trends and associated factors using Demographic and Health Survey dataResearch in context - David Jean Simon; Vénunyé Claude Kondo Tokpovi; Adama Ouedraogo; Kassoum Dianou; Ann Kiragu; Comfort Z. Olorunsaiye; Bénédique Paul (EClinicalMedicine, 2025)
Summary: Background: Pregnant women are at increased risk of intimate partner violence (IPV), with harmful outcomes for both mother and unborn baby. As this public health issue remained poorly documented in low- and middle-income countries (LMICs), this comprehensive study aimed to investigate prevalence and disparities of intimate partner violence during pregnancy (IPVDP) in 57 LMICs, grouped into WHO Regions and World Bank 2022 Income Classification. We also examined changes in IPVDP in LMICs and associated factors. Methods: Data for this study were extracted from Demographic and Health Surveys conducted in 57 LMICs from 2000 to 2024. Countries without domestic violence data were excluded from the study. We estimated overall, regional, sub-regional, and national-weighted prevalence of IPVDP among women aged 15–49 years. Trends in IPVDP were calculated at the national level using the average annual rate of change (AARC) in a subset of 31 countries with at least two survey rounds. A Poisson regression model was fitted for identifying factors associated with IPVDP. Findings: The study included a total weighted sample of 601,534 women. The pooled prevalence of IPVDP was 6.3% (95% CI 6.2–6.4). The Eastern Mediterranean region recorded the highest prevalence of IPVDP (11.3% [95% CI 10.8–11.9]), while the South-East Asia region (3.3% [95% CI 3.0–3.5]) the lowest. Similarly, low-income countries (LICs) reported the highest prevalence of IPVDP (8.2% [95% CI 7.9–8.4]). Further, prevalence varied greatly across countries, ranging from 1.1% (95% CI 0.6–1.5) in South Africa to 17.6% (95% CI 15.3–20.0) in Papua New Guinea. Examining AARC, most countries (23/31) experienced a decreasing trend in IPVDP, however, seven countries showed increasing trends, with the largest of 8.3% (95% CI 6.8–9.9) in Gambia and the smallest of 0.6% (95% CI –0.7 to 1.8) in the Democratic Republic of Congo. Similarly, we found that women: aged 15–19 years, from poor households, with primary education and below, who had more than 5 children, married before 18, who had not participated in household decision-making, and whose partners exhibited controlling behaviour had higher likelihood of experiencing IPVDP. Interpretation: Despite the implementation of numerous development programs aimed at reducing violence against women in LMICs in recent decades, IPVDP remains high in some countries and has even increased in others. Our findings indicate that efforts to reduce IPVDP and the associated health burdens need to be improved in many LMICs. In alignment with the 5.2 Sustainable Development Goal target (i.e., eliminate all forms of violence against women and girls), stakeholders such as NGOs and policymakers can use these findings to roll out interventions based on observed geographic and socio-demographic inequities to end IPVDP among vulnerable groups. Funding: The Fonds de Recherche du Québec-Santé (2022–2023—BF15—314279).